GERAKAN SERAH (SADARI PENTINGNYA TABLET TAMBAH DARAH) DI PUSKESMAS LIANG ANGGANG BANJARBARU, KALIMANTAN SELATAN: Serah Movement (Realize the Importance of Blood Supplement Tablets) in Liang Anggang Health Center, Banjarbaru, South Kalimantan - Mardiati, Nurul; Tangkas, Hansel Hens; Hayati, Winda (Program Studi Sastra Indonesia Universitas Mulawarman, 2024)
Abstract: Anemia is a nutritional problem that needs special attention. Anemia can be caused by iron deficiency, vitamin B12 deficiency, folic acid deficiency, infectious diseases, congenital factors and bleeding. Therefore, Blood Addition Tablets (TTD) are needed to prevent and overcome anemia. One of the services provided at the Liang Anggang Health Center is Maternal and Child Health (MCH) services. However, some patients, especially pregnant women, complained about the side effects they felt, such as nausea and stomach cramps so that patients stopped using blood supplement tablets. The methods used in this health promotion are printed media in the form of leaflets and direct explanations to people who are waiting in line for examination. The sample selection method uses accidental sampling. The results of the